2010
DOI: 10.1016/j.infbeh.2009.10.003
|View full text |Cite
|
Sign up to set email alerts
|

Infant object categorization transcends diverse object–context relations

Abstract: Infants’ categorization of objects in different object-context relations was investigated. The experiment used a multiple-exemplar habituation-categorization procedure where 92 6-month-olds formed categories of animals and vehicles embedded in congruent, incongruent, and homogeneous object-context relations. Across diverse object-context relations, infants habituated to multiple exemplars within a category and categorized novel members of both animal and vehicle categories. Infants showed a slight advantage fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
6
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 21 publications
(8 citation statements)
references
References 46 publications
2
6
0
Order By: Relevance
“…The infants who played with the heterogeneous toys touched objects forming basic-level categories but not superordinate-level categories, whereas the infants who played with the homogeneous toys touched objects forming both basic-level and superordinate categories. These and other results (e.g., Bornstein & Arterberry, 2010; Bornstein, Arterberry, & Mash, 2010; Mareschal & Tan, 2008) suggest that category variability may indeed affect infants’ categorization behavior.…”
supporting
confidence: 67%
“…The infants who played with the heterogeneous toys touched objects forming basic-level categories but not superordinate-level categories, whereas the infants who played with the homogeneous toys touched objects forming both basic-level and superordinate categories. These and other results (e.g., Bornstein & Arterberry, 2010; Bornstein, Arterberry, & Mash, 2010; Mareschal & Tan, 2008) suggest that category variability may indeed affect infants’ categorization behavior.…”
supporting
confidence: 67%
“…Only one published study examined infants’ attention to the relation between figure and context by using pictures of animals and vehicles on various grounds (Bornstein, Arterberry, & Mash, 2010). They found that 6-month-old infants categorized colored photographs of animals and vehicles across various contexts in which the figures appeared (e.g., a tiger in the green field, a tiger on a beach, and a tiger in a parking lot).…”
Section: Resultsmentioning
confidence: 99%
“…These age groups were chosen to parallel those in the dynamic figure and ground discrimination studies (Experiment 1a). Also, given the findings of Bornstein et al (2010), we expected that infants at these ages might be able to detect changes in figures and ground in static pictures. We expected that 1) there would be no a priori preference to static scenes before familiarization to a specific figure or ground; 2) similar to the dynamic experiments, in general, infants should look longer to the novel figure or the novel ground at test; 3) English-reared infants might not be sensitive to different ground distinctions (i.e., within- vs. across-category distinctions) in static events that no longer have a temporal dimension; and 4) infants might detect grounds earlier than they did in dynamic events, due to the presence of a static figure which might not attract as much attention as a dynamic figure.…”
Section: Resultsmentioning
confidence: 99%
“…Recent research has shown that infants form categories of these types of event components within the context of static events. For example, Bornstein et al (2010) finds that 6-month-olds can form categories of figures across different external contexts, or grounds, in static photographs. But, when and how do infants form categories of figure, ground, source and goal in the flow of dynamic events?…”
Section: Discussionmentioning
confidence: 99%
“…By 6 months of age infants form categories of containment relations and by 14 months they form categories of support relations (see Casasola, 2008 for a review; Casasola, 2005; Casasola & Cohen, 2002; Casasola, Cohen & Chiarello, 2003; McDonough, Choi & Mandler, 2003). Finally, infants can represent both the sources and goals (Lakusta & Landau, 2005; Lakusta, Wagner, O’Hearn, & Landau, 2007; Wagner & Lakusta, 2009) and figures and grounds in dynamic motion events (Göksun, Hirsh-Pasek & Golinkoff, 2009; also see Bornstein, Arterberry & Mash, 2010 for infants’ categorization of figures across different contexts, or grounds, in static events).…”
mentioning
confidence: 99%